1999
DOI: 10.4269/ajtmh.1999.60.167
|View full text |Cite
|
Sign up to set email alerts
|

Management of childhood diarrhea and use of oral rehydration salts in a suburban West African community.

Abstract: Abstract. In a household survey in Guinea-Bissau, 319 episodes of diarrhea in children were followed by interviews every second day with the aim of investigating perceived morbidity and subsequent actions taken. The majority of the mothers had good knowledge of oral rehydration salts (ORS). However, only 58% of the episodes were treated with ORS and the amount given was insufficient. Mothers with no knowledge of ORS did not use it during the observed attack of diarrhea regardless of contact with a health cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
2
15
1
1
Order By: Relevance
“…This finding is in agreement with studies done in Guniea – Bissau [14] and Nigeria [9], where caregivers who gave ORT for their children at any time in the past were more likely to use ORT during the current episode of diarrhea. This may be explained by the fact that familiarity with ORT could be gained through experience.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with studies done in Guniea – Bissau [14] and Nigeria [9], where caregivers who gave ORT for their children at any time in the past were more likely to use ORT during the current episode of diarrhea. This may be explained by the fact that familiarity with ORT could be gained through experience.…”
Section: Discussionsupporting
confidence: 92%
“…A recent review of literature showed that only 39% of the children with diarrhea in developing countries receive ORT [5]. Some studies have found that maternal perception of the causes of diarrhea, perception of ORT usefulness, barriers regarding its preparation were associated with ORT use [14-16]. Other studies indicated the relationship of ORT use with maternal education, residence, income of the household and age of the patient [15,17-19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand attribution of serious systemic signs and symptoms to teething may result in delayed management and in some cases to death. Findings fromthis study showed that a vast majority of mothers (96%) attribute child ailment to teething which coincide with OG et al (95.2%) (11), higher than Oyejide et al 58 % ( 12) This misconception is prevalent not only in Sudan but also in other parts of the world, especially east Africa like Nigeria(11)Guinea Bissau (13) and Ethiopia (14) The finding of this study showed that majority of mothers (80.3%) believed that diarrhoea in infants was caused by teething which coincide with other study done in Sudan (90%) (15). These strong mothers' beliefs to attribute infants symptoms to teething contrast the finding of most of contemporary researchers, who did not confirm this strong association and conclude that the symptoms may occur contemporaneously with teething,and only weak association may exist (16,17,18).…”
Section: Discussionmentioning
confidence: 58%
“…Kenya et al demonstrated a positive effect of communication campaigns on knowledge and acceptability of ORS within a district in Kenya [23]. A study of an intervention providing direct distribution of ORS in Guinea-Bissau showed that availability of the product and educational sessions improved ORS uptake [24]. Ross-Degnan et al concluded that similar educational campaigns can influence pharmacists, as an intervention for Kenyan pharmacists was linked to increased sale of ORS and a decline in the use of antibiotics to treat diarrhea [25].…”
Section: Discussionmentioning
confidence: 99%